2012
DOI: 10.1111/j.1461-0248.2012.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐flow between niches facilitates local adaptation in sexual populations

Abstract: In sexual populations, gene-flow between niches is predicted to have differential consequences on local adaptation contingent upon the nature of trade-offs underlying local adaptation. Sex retards local adaptation if antagonistic pleiotropy underlies trade-offs, but facilitates adaptation if mutation accumulation underlies trade-offs. We evaluate the effect of sex in heterogeneous environments by manipulating gene-flow between two niches in sexual and asexual populations using steady-state microcosm experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Further, theory predicts that outcrossing may be favored in the context of frequent migration because sex can break down unfavorable genetic associations that are introduced from outside populations (Agrawal, 2009; Lenormand & Otto, 2000). An experimental evolution study in which sexual and asexual yeast populations were subjected to varying levels of migration between two different selective environments showed that only the sexual populations that experienced migration adapted to both environments (Gray & Goddard, 2012). Therefore, frequent host migration coupled with frequent environmental change may provide the most likely context for the maintenance of outcrossing, apart from host–parasite coevolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, theory predicts that outcrossing may be favored in the context of frequent migration because sex can break down unfavorable genetic associations that are introduced from outside populations (Agrawal, 2009; Lenormand & Otto, 2000). An experimental evolution study in which sexual and asexual yeast populations were subjected to varying levels of migration between two different selective environments showed that only the sexual populations that experienced migration adapted to both environments (Gray & Goddard, 2012). Therefore, frequent host migration coupled with frequent environmental change may provide the most likely context for the maintenance of outcrossing, apart from host–parasite coevolution.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental evolution studies have demonstrated that sex can be favored when populations migrate between heterogeneous environments or adapt to new environments. Gray and Goddard (2012) passaged sexual and asexual yeast populations in two different selective environments with varying levels of migration between the environments. Only the sexual populations that experienced migration exhibited simultaneous adaptation to both environments.…”
Section: Introductionmentioning
confidence: 99%
“…The data reported here suggest a VDE carrier would enjoy increased survival under these conditions. Finally, while we now have a good handle on the reasons that sex is maintained [36][37][38][39], we have less evidence for why sex evolved [18]. Selfish elements may spread through sex, and some ideas suggest that selfish elements drove the initial evolution of sex [17].…”
Section: Discussionmentioning
confidence: 99%
“…When individuals sampled from discrete points (such as similar geographic locations or niches) tend to be more closely related to one another than between points, this supplies evidence of population structure. Subgroups isolated by barriers to gene flow will become increasingly differentiated by the processes of mutation, selection and drift but sufficient gene flow between subgroups will serve to homogenise groups into a single population [5][7]. Classic population genetics methods estimate the combined effect of these processes to infer the extent of population subdivision by analysing allele frequencies within and between sampled populations, that may or may not be differentiated [8].…”
Section: Introductionmentioning
confidence: 99%